2010
DOI: 10.1002/bit.22841
|View full text |Cite
|
Sign up to set email alerts
|

Complete anaerobic mineralization of pentachlorophenol (PCP) under continuous flow conditions by sequential combination of PCP‐dechlorinating and phenol‐degrading consortia

Abstract: Complete mineralization of 50 µM of pentachlorophenol (PCP) was achieved anaerobically under continuous flow conditions using two columns connected in series with a hydraulic retention time of 14.2 days, showing the highest reported mineralization rate yet of 3.5 µM day(-1). The first column, when injected with a reductive PCP dechlorinating consortium, dechlorinated PCP to mainly phenol and traces of 3-chlorophenol (3-CP) using lactate supplied continuously as an electron donor. The second column, with an ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…Additionally, the chemical concentrations used in the synthetic community in this study were much lower than those used in previous reports, i.e. 4 or 20 mM lactate, 20 mM FeO-OH, 20 mM SO 4 2- (Yang et al, 2009;Li et al, 2010Li et al, , 2013, and would avoid excessive resource consumption and decrease cost. Previous studies have reported the microbial degradation of 2,4,6-TBP aerobically or anaerobically (Ahn et al, 2003;Boyle et al, 1999;Uhnakova et al, 2009;Yamada et al, 2008).…”
Section: Mineralization Of 246-tbp By Combination Of Strain Ds Withmentioning
confidence: 91%
See 4 more Smart Citations
“…Additionally, the chemical concentrations used in the synthetic community in this study were much lower than those used in previous reports, i.e. 4 or 20 mM lactate, 20 mM FeO-OH, 20 mM SO 4 2- (Yang et al, 2009;Li et al, 2010Li et al, , 2013, and would avoid excessive resource consumption and decrease cost. Previous studies have reported the microbial degradation of 2,4,6-TBP aerobically or anaerobically (Ahn et al, 2003;Boyle et al, 1999;Uhnakova et al, 2009;Yamada et al, 2008).…”
Section: Mineralization Of 246-tbp By Combination Of Strain Ds Withmentioning
confidence: 91%
“…In our previous study, we demonstrated the mineralization of pentachlorophenol (PCP) by co-inoculation of multiple consortia: one reductively dechlorinating PCP and another anaerobically oxidizing the dehalogenated metabolites (less-chlorinated phenols) in a batchtype culture (Yang et al, 2009) and continuous-flow reactors (Li et al, 2010. These results indicated that functionallydesigned communities prepared by co-inoculating multiple consortia are a promising application of anaerobic systems.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations